Biochesmistry / [cakera padat] - Mathews, Christopher K., 1937-; Van Holde, Kensal Edward, 1928-; Ahern, Kevin G. (San Francisco : Addison Wesley, 2000)
Sytem requirements: Windows 95/98/NT; or MacOS 7.6.1 or higher.